STEREOTIP GENDER DAN AKUNTAN WANITA - Hidayah, Nurul; Hamidah, Hamidah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.12.TAHUN.2022DO - 10.24843/EEB.2022.v11.i12.p09, 2022)
This research aims to obtain an overview of gender stereotypes by woman accountants based on their experiences in carrying out the duties. This research uses the phenomenological method of Sanders (1982) and five-woman accountants as informants with different professions and positions. The main finding of this research shows that woman accountants who live and work in the Banjar community indicate that some of them still experience gender stereotypes. Gender stereotypes tend to be experienced by woman accountants who are married and live in remote areas. Although the participation of women as accountants has been quite good, the dominance of men is still felt in some organizations. When gender stereotypes are assosicated with the liberal feminist theroy, it is found that when women accountants get the same opportunities as men, they will implement their potential and show that they are just as effective as men. Therefore, society and organizations play an important role in the advancement of women.